Belajar Sambil Bermain: Penerapan Model Game Based Learning Berbantuan Wordwall Untuk Meningkatkan Hasil Belajar IPAS Kelas IV - RITA ARINI; Sundahry; Randi Eka Putra (CV. DIGITIAL EDUKASI NUSANTARA, 2026)
Abstract This research is motivated by the low learning outcomes of science and natural sciences, namely 34.7% of students in grade IV of SDN 187/II Kuning Gading. This study aims to improve science and natural sciences learning outcomes through the application of the Game Based Learning model assisted by Wordwall. The method uses Classroom Action Research (CAR) through two cycles. The research sample is 23 students. Data were collected through observation, tests, and documentation. The results show an increase in teacher performance from cycle I 84.6% cycle II increased 100% and learning completeness from cycle I 69.5% cycle II increased 91.3%. Student activity is consistently in the good to very good category. The Game Based Learning model is an alternative game-based learning model that is proven to be able to improve students' science and natural sciences learning outcomes in grade IV of SDN 187/II Kuning Gading. This research contributes to the innovation of interesting and interactive technology-based learning, as well as increasing student active involvement, creating a fun learning atmosphere, so as to encourage student-centered learning. The integration of the Game Based Learning model with interactive digital media in the form of Wordwall provides innovation in helping students understand the abstract concept of map material in science learning in grade IV. Therefore, it can be concluded that the use of technology in learning not only has an impact on improving learning outcomes, but also increases students' readiness to face technological developments in the digital era, as well as making it easier for students to understand abstract material through visualization and more interactive learning media. Keywords: Learning Outcomes; Cognitive Science; Game Based Learning; Wordwall.